2011
DOI: 10.1073/pnas.1010310108
|View full text |Cite
|
Sign up to set email alerts
|

Transition from one-dimensional water to ferroelectric ice within a supramolecular architecture

Abstract: Ferroelectric materials are characterized by spontaneous electric polarization that can be reversed by inverting an external electric field. Owing to their unique properties, ferroelectric materials have found broad applications in microelectronics, computers, and transducers. Water molecules are dipolar and thus ferroelectric alignment of water molecules is conceivable when water freezes into special forms of ice. Although the ferroelectric ice XI has been proposed to exist on Uranus, Neptune, or Pluto, evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 47 publications
0
38
0
1
Order By: Relevance
“…It was recently suggested that a temporary memory effect can accompany the evolution of polarization in these systems 107 . This ferroelectric ordering may indeed be possible, given that some ferroelectric ice structures have already been reported [108][109][110] , particularly in confined environments such as MOFs 111 . Despite the observation of ferroelectricity in blood vessels and hybrid materials, protein-based ferroelectrics have not yet been reported.…”
Section: Perspectivementioning
confidence: 76%
“…It was recently suggested that a temporary memory effect can accompany the evolution of polarization in these systems 107 . This ferroelectric ordering may indeed be possible, given that some ferroelectric ice structures have already been reported [108][109][110] , particularly in confined environments such as MOFs 111 . Despite the observation of ferroelectricity in blood vessels and hybrid materials, protein-based ferroelectrics have not yet been reported.…”
Section: Perspectivementioning
confidence: 76%
“…Breaking of the bulk symmetry, as occurs at surfaces and in nanostructures, has the potential to induce proton ordering by eliminating the near-degeneracy of structures with water molecules in different orientations 38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…Since this temperature range is close to the glass transition temperature of supercooled water embedded in nano-porous or polymer systems 1215 , the dielectric behaviour for [ 1 ](ClO 4 ) 2 ∙ n H 2 O is most likely due to the molecular dynamics triggered by dipolar water molecules existing in the anionic cluster of {ClO 4 − } 10 . It has been recognized that water molecules confined in nano-pores can form a supercooled liquid state to give a rather large dielectric response 16,17 . However, such dynamics in a metastable liquid state has been realized only in wet conditions obtained by exposing framework materials to water.…”
Section: Introductionmentioning
confidence: 99%